A retinal snap shot may indicate individual risk for cardiovascular disease — The MIPH Eye&Health Study. (1st February 2015) - Schuster, Alexander Karl-Georg; Fischer, Joachim Ernst; Vossmerbaeumer, Urs
Abstract: Background: Examination of retinal vasculature can be used to non-invasively quantify changes within the microvasculature of the human body and might be a predictor of cardiovascular disease. This study evaluates associations of the structure of the retinal vasculature with established risk factors for cardiovascular disease. Methods: A cross-sectional study was performed in a working age population. Several systemic cardiovascular parameters were analyzed and PROCAM- and SCORE-risk estimates were calculated. A quantitative ophthalmological examination including digital fundus imaging has taken place. Central retinal arterial/venous equivalents (CRAE/CRVE) and arterio-venous ratio (AVR) were analyzed using validated software. Associations of retinal vessel parameters and systemic cardiovascular and ocular parameters were calculated by multivariate analysis using SPSS software. A p-value of < 0.05 with Bonferroni correction was accepted as significant. Results: 338 probands were included. A smaller CRAE was independently associated with increased mean arterial blood pressure, higher age and higher body-mass index. Regarding CRVE age was inversely associated. Other cardiovascular risk parameters were not associated to the examined retinal vessel equivalents. AVR showed a significant association to mean arterial blood pressure and body-mass-index. PROCAM- and SCORE-risk estimates were negatively associated with CRAE and AVR, but not associated to CRVE. Conclusions: Arterial retinal vessel analysis and AV-ratio showed associations to established cardiovascular parameters in the study population. PROCAM- and SCORE-risk estimates as indicators of cardiovascular risk were associated with the CRAE and the AV-ratio. This suggests that a single snap shot of the retinal vessels may indicate the individual relative risk for cardiovascular events. Highlights: Arterial retinal vessel analysis is associated with cardiovascular factors. PROCAM-score is linked to the arterial retinal vessel analysis and the AV-ratio. A single retinal snap shot may indicate the risk for cardiovascular events.